THE BUDGETING AND FUND MANAGEMENT SYSTEM OF GIOK AGUNG BAITUL A’LA MOSQUE IN NAGAN RAYA REGENCY ACCORDING TO THE IDÂRAH CONCEPT - Hidayat, Muhammad Ryan; Muhammad Iqbal (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This study aims to evaluate the budgeting and financial management system of the Giok Agung Baitul A'la Mosque in Nagan Raya Regency based on the principles of Islamic management (idârah). The study employs a descriptive qualitative approach, utilising data collection techniques that include in-depth interviews, field observations, and documentary studies. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the mosque's financial management system has reflected some of the principles of idârah, particularly in the aspects of takhṭīṭ (planning) and tanzhīm (organisation), as evidenced by the implementation of annual meetings and the distribution of tasks among the management. However, the absence of formal documents, such as the Mosque Revenue and Expenditure Budget Plan (RAPBM), and the lack of written Standard Operating Procedures (SOPs), constitute the main weaknesses in formal planning. Financial management is still carried out manually and does not fully comply with the principle of accountability. From the idârah perspective, the aspects of tawjīh (direction), taqwīm (supervision), and mutāba‘ah (monitoring) have not been optimally implemented due to limited training, an unstructured supervision system, and a lack of regular monitoring. Nevertheless, values such as trustworthiness, responsibility, and community participation have become social strengths that can serve as a foundation for developing a more professional, transparent, and sustainable mosque management system under Islamic principles.